Correction to: Techniques for Turbulence Tripping of Boundary Layers in RANS Simulations (Flow, Turbulence and Combustion, (2022), 108, 3, (661-682), 10.1007/s10494-021-00296-5) - Tabatabaei, Narges; Vinuesa, Ricardo; Orlu, Ramis; Schlatter, Philipp (Flow Turbulence and Combustion, 2022)
The original article has been corrected.
CRIS-Team Scopus Importer:2023-03-21